PERSEPSI MAHASISWA TERHADAP VIRTUAL MICROSCOPE BATUAN PADA MATA KULIAH GEOLOGI UMUM - Rosi Natalia; Susilowaty , Nora (Global Action and Education for Society, 2025)
This study aims to describe students' mathematical critical thinking ability according to their ability level, namely high, medium, low on the material of worth comparison and inverse value comparison. “This type of research is descriptive qualitative research. The samples in this study were 34 students from class VII C SMP Negeri Parongpong. The subjects of this study were 3 students. Data collection was in the form of written tests and interviews. The results of this study indicate that students at a high level of mathematical critical thinking ability are able to complete 3 indicators of critical thinking ability, namely interpretation, evaluation and inference, while for the analysis indicator students are still confused about how to make the mathematical model. For students' mathematical critical thinking skills at the medium level, they can fulfill 2 indicators of critical thinking skills including interpretation and inference, while for the analysis indicator students have not been able to identify the problem and on the evaluation indicator students lack understanding in using strategies in solving problems”. students with low levels of critical thinking ability, mastery of critical thinking indicators is limited to interpretation. Meanwhile, the indicators of analysis, evaluation, and inference show a low level of understanding, despite the maximum efforts that students have made in answering the questions.